The Influence of Competence, Independence, and Supervision on Dysfunctional Audit Behavior (Case Study at the BPK Representative Office of West Java Province) - Dewi, Laura Evita; Paulus, Sugiono; Harahap, Devianti Yunita (PT Mattawang Mediatama Solution, 2024)
The purpose of this study is to analyze the three variables—competence, independence, and supervision—that influence dysfunctional audit behavior. It examines whether competence, independence, and supervision influence dysfunctional audit behavior directly and/or indirectly. Data were collected from 60 respondents/auditors from the BPK Representative Office of West Java Province using simple random sampling and analyzed with SPSS 26.0. The findings reveal that competence and independence have a significant and direct negative influence on dysfunctional audit behavior, while supervision does not have a direct influence on dysfunctional audit behavior. Furthermore, supervision through competence and independence has an indirect influence on dysfunctional audit behavior. To obtain a more complete view and recommendations for future BPK improvements, it is advised that future research be conducted using a more holistic approach for the BPK as an organization, using the same or appropriate factors.